RAC-LATS1/2 signaling regulates YAP activity by switching between the YAP-binding partners TEAD4 and RUNX3. - Jang, J.W.; Kim, M.K.; Lee, Y.S.; Lee, J.W.; Kim, D.M.; Song, S.H.; Lee, J.Y.; Choi, B.Y.; Min, B.; Chi, X.Z.; Bae, S.C. (Oncogene, 2017)
The tumor-suppressor RUNX3 has a critical role in a lineage determination, cell cycle arrest and apoptosis. Lozenge (Lz), a Drosophila homolog of mammalian RUNX family members, has integral roles in these processes and specifically in eye cell fate determination. To elucidate the genetic modifiers of Lz/RUNX3, we performed a large-scale functional screen in a fly mutant library. The screen revealed genetic interactions between the Lz, Rac and Hippo pathways. Analysis of interactions among these genes revealed that the defective phenotype resulting from activation of Yki, an end point effector of the Hippo pathway, was suppressed by Lz and enhanced by Rac-Trio. Molecular biological analysis using mammalian homologs reveled that LATS1/2-mediated YAP phosphorylation-facilitated dissociation of the YAP-TEAD4 complex and association of the YAP-RUNX3 complex. When cells were stimulated to proliferate, activated RAC-TRIO signaling inhibited LATS1/2-mediated YAP phosphorylation; consequently, YAP dissociated from RUNX3 and associated with TEAD, thereby replacing the YAP-RUNX3 complex with YAP-TEAD. RUNX3 contributed to both association and dissociation of YAP-TEAD complex, most likely through the formation of the YAP-TEAD-RUNX3 ternary complex. Ectopic expression of RUNX3 in MKN28 gastric cancer cells reduced tumorigenicity, and the tumor-suppressive activity of RUNX3 was associated with its ability to interact with YAP. These results identify a novel regulatory mechanism, mediated by the Hippo and RAC-TRIO pathways, that changes the binding partner of YAP.